Robust Humoral and Cellular Immune Responses to Pertussis in Adults After a First Acellular Booster Vaccination - van der Lee, Saskia; van Rooijen, Debbie M.; de Zeeuw-Brouwer, Mary-Lène; Bogaard, Marjan J. M.; van Gageldonk, Pieter G. M.; Marinovic, Axel Bonacic; Sanders, Elisabeth A. M.; Berbers, Guy A. M.; Buisman, Anne-Marie (Frontiers in Immunology, 2018)
Introduction: To reduce the pertussis disease burden, nowadays several countries recommend acellular pertussis (aP) booster vaccinations for adults. We aimed to evaluate the immunogenicity of a first adult aP booster vaccination at childbearing age. Methods: In 2014, healthy adults aged 25–29 years (n = 105), vaccinated during infancy with 4 doses of whole-cell pertussis (wP) vaccine, received a Tdap (tetanus, diphtheria and aP) booster vaccination. Blood samples were collected longitudinally pre-booster, 2 and 4 weeks and 1 and 2 years post-booster. Tdap vaccine antigen-specific antibody levels and memory B- and T-cell responses were determined at all time points. Antibody persistence was calculated using a bi-exponential decay model. Results: Upon booster vaccination, the IgG levels specific to all Tdap vaccine antigens were significantly increased. After an initial rapid decline in the first year, PT-IgG antibody decay was limited (15%) in the second year post-booster. The duration of a median level of PT-IgG ≥20 IU/mL was estimated to be approximately 9 years. Vaccine antigen-specific memory B- and T-cell numbers increased and remained at high levels although a significant decline was observed after 4 weeks post-booster. However, Th1, Th2 and Th17 cytokine production remained above pre-booster levels for 2 years. Conclusions: The Tdap booster vaccination in wP-primed Dutch adults induced robust long-term humoral and cellular immune responses to pertussis antigens. Furthermore, PT-IgG levels are predicted to remain above the presumed protective cut-off for at least 9 years which might deserves further attention in evaluating the current recommendation to revaccinate women during every new pregnancy.